Role of Porphyromonas gingivalis in oral squamous cell carcinoma development: A systematic review - Lafuente Ibáñez de Mendoza, Irene; Maritxalar Mendia, Xabier; García de la Fuente, Ana María; Quindós Andrés, Guillermo; Aguirre Urizar, José Manuel (Journal of periodontal research, 2020)
Objective The target of the current systematic review is to gather and synthesize the most recent scientific information about the role of Porphyromonas gingivalis in the molecular pathways of oral squamous cell carcinoma (OSCC). Background Oral squamous cell carcinoma is the most common malignancy of the oral cavity, with a poor prognosis and a low survival rate. Etiology is multifactorial but consumption of tobacco and alcohol is the most important risk factors. P gingivalis is a Gram‐negative anaerobic bacterium commonly found in oral microbiota that has been linked to periodontal disease (PD), and recently to OSCC. However, its association with OSCC development is not well defined. Material and methods A bibliographic research was carried out selecting articles published until 2019, on PubMed, Web of Science, and Scopus databases, with the keywords “Porphyromonas gingivalis,” “oral cancer,” “oral squamous cell carcinoma,” and “periodontal pathogen.” Results Seventeen articles, 14 in vitro and three in animal models, were selected. Models mimicking OSCC were OSCC pre‐established cell lines (11 studies), OSCC/ healthy human biopsies (three studies), and animals with OSCC (three studies). P gingivalis strains used to cause infection in these studies were ATCC 33277, 381, and W83. Conclusions Porphyromonas gingivalis could play an important role in OSCC development and could be involved in three different stages: epithelial‐mesenchymal transition of malignant cells, neoplastic proliferation, and tumor invasion. Current findings emphasize the convenience of treatment and control approaches of PD as part of the primary prevention of OSCC.